2023
DOI: 10.1002/1878-0261.13354
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic pan‐cancer analysis using rank‐based Bayesian inference

Abstract: The analysis of whole genomes of pan‐cancer data sets provides a challenge for researchers, and we contribute to the literature concerning the identification of robust subgroups with clear biological interpretation. Specifically, we tackle this unsupervised problem via a novel rank‐based Bayesian clustering method. The advantages of our method are the integration and quantification of all uncertainties related to both the input data and the model, the probabilistic interpretation of final results to allow stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…Furthermore, a study using rank-based Bayesian clustering to analyze pan-cancer identi ed three pansquamous clusters consist of LUSC, head and neck squamous cancer, and bladder cancer [37]. Vitelli et al found that these three cancers were not clustered based on tissue of origin, but on cell morphology [37]. They suggested that some tumors should be classi ed according to tissue type not the same tissue of origin [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a study using rank-based Bayesian clustering to analyze pan-cancer identi ed three pansquamous clusters consist of LUSC, head and neck squamous cancer, and bladder cancer [37]. Vitelli et al found that these three cancers were not clustered based on tissue of origin, but on cell morphology [37]. They suggested that some tumors should be classi ed according to tissue type not the same tissue of origin [37].…”
Section: Discussionmentioning
confidence: 99%
“…Vitelli et al found that these three cancers were not clustered based on tissue of origin, but on cell morphology [37]. They suggested that some tumors should be classi ed according to tissue type not the same tissue of origin [37]. This may explain bladder cancer increased risk of LUSC rather than LUAD.…”
Section: Discussionmentioning
confidence: 99%